Evaluation of the Genetic Toxicity of Aqueous and Alcoholic Extracts of Seeds of Peganum harmala L. on Onion root (Allium cepa L.) - Saif M. Ibrahim; Nidhal N. Hussein (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The genetic toxicity of aqueous and alcoholic extracts of seeds of Peganum harmala L. was evaluated on the onion roots ,using  concentrations 10,25,50,100 and 200 % w/v of extracts and periods of exposure 24,48 and 74 hours. The results indicated that the Peganum harmala significantly decreased root growth rate of onion root at all concentrations and treatment periods in comparison to the control ,  the growth of the root decreased when increasing the extract concentration.The EC50value  of aqueous extracts was 50% and for alcohol extract was 25% ,thus the alcohol extract was most effective in the growth rate of the roots from the aqueous extract. The results also indicated that the mitotic index of Allium cepa was significantly decreased when treated with aqueous and  alcoholic extract,the mitotic index decreased when increasing the extract concentration. It was further noted that the mitoticindex was not significantly affected by increasing exposure periods.As the concentrations 25 and100% of aqueous and alcohol extracts respectively decrease MI below 50% in comparison with control ,these concentrations are considered semi lethal,while the concentration 200% for aqueous and alcoholic extract decrease the MI below 22% to the control  considered lethal..Results showed that Peganum harmala seed extracts significantly decreased the prophase and significantly increased the Metaphase. High percentage of chromosomal aberrations ,in onion root was observed , which increased by increasing concentrations of extracts .The more chromosomal aberrations observed (stickiness, bridges, disturbed chromosome, and C-mitosis) ,the less frequent abnormalities observed (Shifting of poles, star chromosome, lagging chromosome and Polyploidy).